Calgary Family Assessment Model (CFAM) Keluarga tentang Penanganan Pertama Food Borne Disease Anak - Wiwit Dwi Nurbadriyah (Journal of Ners and Midwifery, 2015)
Food borne disease (FBD) is a disease through consumption of contaminated food. The problem is that, school children are vulnerable to FBD because of household food contamination. This indicates the family as a food handler hygiene mainly the mother who prepare the food needed to be improved. Most common FBD is diarrhea, one of the danger is that the child’s body fluids are expelled out through the stool this can cause dehydration or even death. Family plays very important role in the handling of FBD first before being taken to the health service. This can be known through family studies approach CFAM (Calgary Family assessment model). The design of this study was descriptive eksplorative with a sample of 35 respondents; the 4th graders and their parents (17 persons) and 5th graders and their parents (18) in Jatirejoyoso Kepanjen Elemetary School through purposive sampling technique. The data taken were demographic and CFAM consists of the structural assessment components, development as well as family function. The family in first handling of food borne disease largely was not routine (71.4%). Ways of solving the problems mostly by the head of the family (74.3%). Responsible care for sick children mostly (57.2%) by only one parent (father / mother). Follow up during sick mostly made an effort (curative) as much as 85.7%. Family belief the majority (80%) considered that the first treatment at home was not needed because it could be taken directly to the health service. Health workers are expected to provide guidance for families through health volunteers on first handling practices of FBD. While schools are expected to perform optimization of UKS (School Health Unit) program to provide health education about the prevention and first treatment of FBD toward the school community.